2009
DOI: 10.1128/aac.00426-09
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of High Levels of Extended-Spectrum-β-Lactamase-Producing Gram-Negative Bacilli in the Asia-Pacific Region: Data from the Study for Monitoring Antimicrobial Resistance Trends (SMART) Program, 2007

Abstract: Of 3,004 gram-negative bacilli collected from intra-abdominal infections in the Asia-Pacific region during 2007, 42.2% and 35.8% of Escherichia coli and Klebsiella spp., respectively, were extended-spectrum ␤-lactamase (ESBL) positive. Moreover ESBL rates in India for E. coli, Klebsiella pneumoniae, and Klebsiella oxytoca were 79.0%, 69.4%, and 100%, respectively. ESBL-positive E. coli rates were also relatively high in China (55.0%) and Thailand (50.8%). Ertapenem and imipenem were the most active drugs teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 13 publications
8
128
3
2
Order By: Relevance
“…But perhaps most importantly, we found an even higher proportion of E. coli producers of ESBL in the isolates examined in here. This finding corresponds with previous studies not only in the Latin American region [15], but also from the Asia/ Pacific region (where India, China and Thailand reported the highest prevalence rates of ESBL-producing E. coli: 79.0%, 55.0% and 50.8% respectively [25]). In contrast, the results from this study differ from those conducted in other parts of the world, mainly North America and Europe; for example, in a study performed in Scotland on enterobacteriaceae isolates, only 7.5% of the isolates were phenotypically confirmed ESBL producers [26].…”
Section: Discussionsupporting
confidence: 80%
“…But perhaps most importantly, we found an even higher proportion of E. coli producers of ESBL in the isolates examined in here. This finding corresponds with previous studies not only in the Latin American region [15], but also from the Asia/ Pacific region (where India, China and Thailand reported the highest prevalence rates of ESBL-producing E. coli: 79.0%, 55.0% and 50.8% respectively [25]). In contrast, the results from this study differ from those conducted in other parts of the world, mainly North America and Europe; for example, in a study performed in Scotland on enterobacteriaceae isolates, only 7.5% of the isolates were phenotypically confirmed ESBL producers [26].…”
Section: Discussionsupporting
confidence: 80%
“…Some investigators continue to support the importance of knowing the ESBL status in an isolate to ensure proper therapy [5,6]. Especially in ESBL-endemic areas, where therapeutic options are very limited due to associated co-resistance in other classes of antimicrobial agents [7,8]. Moreover, in a survey on 144 infectious disease specialists, most respondents reported that they would not treat Enterobacteriaceae infections based on the current breakpoints alone without testing for ESBL [9].…”
Section: Introductionmentioning
confidence: 99%
“…Reports from SMART in the Asia-Pacific region showed certain countries to be associated with the highest levels of antimicrobial resistance among these pathogens globally. Extended-spectrum b-lactamase (ESBL) production by strains of Escherichia coli and Klebsiella pneumoniae in countries such as Thailand, China, and India have been documented to be 53.0% and 23.1%, 65.% and 31.9% and 67.0% and 55.0%, respectively [9][10][11][12].…”
mentioning
confidence: 99%